2020
DOI: 10.1093/mnras/staa785
|View full text |Cite
|
Sign up to set email alerts
|

The rotation of α Oph investigated using polarimetry

Abstract: Recently we have demonstrated that high-precision polarization observations can detect the polarization resulting from the rotational distortion of a rapidly rotating Btype star. Here we investigate the extension of this approach to an A-type star. Linearpolarization observations of α Oph (A5IV) have been obtained over wavelengths from 400 to 750 nm. They show the wavelength dependence expected for a rapidly-rotating star combined with a contribution from interstellar polarization. We model the observations by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 56 publications
4
36
0
Order By: Relevance
“…Earlier Marshall et al (2016) found λmax to be between 35 nm and 600 nm with a most probable value of 470 nm from 2-band observations of a few stars at Southern declinations. Lastly, in investigating the rotational properties of α Oph, Bailey et al (2020b) found 440 ± 110 nm for that star. Multi-band data was taken for HD 167425 and HD 162521.…”
Section: Wavelength Dependencementioning
confidence: 92%
See 2 more Smart Citations
“…Earlier Marshall et al (2016) found λmax to be between 35 nm and 600 nm with a most probable value of 470 nm from 2-band observations of a few stars at Southern declinations. Lastly, in investigating the rotational properties of α Oph, Bailey et al (2020b) found 440 ± 110 nm for that star. Multi-band data was taken for HD 167425 and HD 162521.…”
Section: Wavelength Dependencementioning
confidence: 92%
“…The Serkowski Law gives a redder, more tightly defined λmax, but K is not particularly well defined. The past studies of the interstellar medium (Marshall et al 2016;Cotton et al 2019a;Bailey et al 2020b) have found values of λmax more closely aligned with the Serkowski-Wilking Law fit, and so values of λmax equal to 472.6 nm and K equal to 0.79 are adopted.…”
Section: Wavelength Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…HIPPI-2 and Mini-HIPPI were both used in the study of the Spica binary system (Bailey et al 2019). HIPPI-2 has also recently been used in the study of the rapidly rotating system α Oph (Bailey et al 2020b), the red supergiant Betelgeuse (Cotton et al 2020a) and the polluted white dwarf G29-38 (Cotton et al 2020b).…”
Section: Observationsmentioning
confidence: 99%
“…It has been used in Earth atmosphere research as well as planetary atmosphere modelling (Bailey et al 2018;Bott et al 2018). In Cotton et al (2017) and Bailey et al (2020b) / was used for modelling the polarization of a rotationally distorted star, and the supplementary materials of the first work included verifications of the methods by comparison with stellar polarization calculations of Harrington (2015) and rotating star polarization models of Sonneborn (1982).…”
Section: Polarized Radiative Transfermentioning
confidence: 99%